Crystallization-induced mechanofluorescence for visualization of polymer crystallization - Sota Kato (Nature Portfolio, 2021)
Residual stress in crystalline polymers can lead to material failure, but currently methods which can quantify residual stress in such materials are lacking. Here, by using fluorescent-type mechanochromophores, the authors develop a method to visualize and quantify low degrees of stress that arises from micro-mechanical forces during polymer crystallization.